Potencial tóxico e anticarcinogênico da alga Prasiola crispa - Zemolin, Ana Paula Pegoraro (2015)
Toxic and anticarcinogenic effects of Prasiola Seaweed extract crispa (PCE) were investigated in Drosophila melanogaster, Nauphoeta cinérea and leukemic cells. In fruit flies, toxicity was assessed as mortality and biochemical changes, including acetylcholinesterase (AChE) and oxidative stress markers. The cardiotoxic action of PCE was examined in a semi-isolated heart model cheap. They were also analyzed the antiproliferative properties of Prasiola crispa (Pc) in leukemic K562 cells. The PCE administration (2 mg / ml) in flies, lasted 24 hours and resulted in a significant increase in mortality (7.6 fold increase compared to control). Activity of AChE (GSH) glutathione levels and the hydroperoxide formation was unchanged. Glutathione S-transferase (GST) and catalase (CAT) were significantly altered after treatment PCE. The fraction III (ethyl acetate) PCE was significantly more toxic to the flies compared to fractions I (methanol) and II (ethanol). A significant decrease in heart function inexpensive semi isolated heart model was observed. Addition of 5,5'-dithiobis acid (2-nitrobenzoic acid (DTNB), an oxidizing agent, concomitantly with the extract significantly blocked this effect. The PCE insecticidal properties can be related to changes in the important antioxidant detoxification system as well as to changes in insect cardiac function. To assess the antiproliferative activities of ethanolic fraction (EF) and ethyl acetate (EAF) of Prasiola crispa extract, cancerous leukemic K562 cells were exposed for 24 hours to different concentrations of PCE fractions. After treatment, cell viability, PARP cleavage and apoptosis Nrf2 expression of HO-1 and HSP70 were determined. The EAF showed a higher cytotoxic activity on leukemic cells as compared to EF. Cell proliferation was inhibited, a fact which was accompanied by a marked increase in the expression of Nrf2, HO-1 and HSP70 protein levels, indicating signs of oxidative stress. The results indicate the potential antitumor effect of Prasiola crispa algae.